2022
DOI: 10.1017/rdc.2022.25
|View full text |Cite
|
Sign up to set email alerts
|

SCALING THE 14C-EXCURSION SIGNAL IN MULTIPLE TREE-RING SERIES WITH DYNAMIC TIME WARPING

Abstract: A signal of rapid changes in 14C production is logged in annual series of 14C derived from tree rings, which can be associated with diverse effects of cosmic-ray fluxes, including solar burst and supernova events. These 14C signatures may vary in time and space. The intensity and structure of the 14C signal is multifaced, which complicates understanding of the forcing and attribution of the underlying astrophysical events. It was suggested that Δ14C in 1052/53 CE and 1054/55 CE signatures at a 4‰–6‰ range over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Thus, multiple publications have reported an unusual 14 C increase around that age, but its origin has not yet been resolved. Panyushkina et al (2022) suggested that these different excursions may all relate to the same event, which is manifested differently in different records.…”
Section: Smaller Events: 1279 Ce 1052 Ce and 5410 Bcementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, multiple publications have reported an unusual 14 C increase around that age, but its origin has not yet been resolved. Panyushkina et al (2022) suggested that these different excursions may all relate to the same event, which is manifested differently in different records.…”
Section: Smaller Events: 1279 Ce 1052 Ce and 5410 Bcementioning
confidence: 99%
“…Rapid 14 C increases were confirmed in 7177/7176 BCE and 5260/5259 BCE in these datasets of three or four tree samples (note that only 14 C data of the Bristlecone pine for the 5259 BCE event depicts the increase one year earlier, i.e., in 5261/5260 BCE). This offset may be due to a dendrochronological miscount or inaccurate separation of annual rings, but Panyushkina et al (2022) have also emphasized the importance of cross-correlating different sequences and correcting for timing differences. For these two events, overall 14 C variations are similar to those of the 774 CE event, with the maximum 14 C increase reaching 19-20‰ in 14 C (deviation of 14 C concentration from a standard of modern value after corrections of age and isotopic fractionation), which is greater than that of the 774 CE event (≈18‰).…”
Section: Introductionmentioning
confidence: 99%